Subtalar joint kinematic correlations with footprint arch index in race walkers - Elvira, J. L. L.; Vera-Garcia, F. J.; Meana, M. (The Journal of Sports Medicine and Physical Fitness, 2008)
Aim: The aim of the paper was to analyze the relationship between footprint arch index and subtalar joint movement in race walkers. Methods: Thirteen young, highly skilled race walkers volunteered to participate. We obtained dominant-foot footprints in a bipedal stance. The arch index was measured to classify arch height. We also conducted a photogrammetric video-3D study on a running track. The support phase was recorded while subjects race walked at their individual competition speed. We calculated 4 angle time series describing the ankle joint kinematics during the support phase. Five specific step instants were calculated for each angle and correlated with the arch index. Race walkers were grouped according to arch height to compare. We also correlated the arch index with the time in medial support, and time to change from lateral to medial support during the stance phase. Results: In the calcaneal angle we found correlations with the footprint (r=0.81; P<0.01) and statistical differences when grouped (P<0.01). In this angle we also found a moderate-high correlation between footprint arch index and the time in medial support (r=0.77; P<0.01), and also in the time to change from lateral to medial support during the stance phase (r=-0.73; P<0.01). Data also show that the race walkers adopt a characteristic propulsion technique in the end of the support. No statistical differences were found in the rearfoot angle, which has been previously associated to specific injuries in running. Conclusion: In conclusion, race walkers with higher arches exhibit a more pronounced support with the lateral side of the foot and they do so for a longer time. Conversely, subjects with flatter feet support with the medial side of the foot. The footprint has been found to be a good predictor for the technique employed with respect to the medial and lateral strike of the foot reflected by the calcaneal angle. Coaches should keep this in mind from both performance and injury prevention viewpoints.